ANALISIS KESALAHAN KONSEP BERDASARKAN GAYA BELAJAR PADA MATERI OPERASI BENTUK ALJABAR - Gulo, Jesinatalinda (Afore : Jurnal Pendidikan Matematika, 2024)
This research was motivated by conceptual errors based on the learning styles of class VII students at SMP Negeri 3 Huruna when completing algebraic operations. This research aims to describe students' conceptual errors based on learning styles in solving algebraic operations problems. This type of research is qualitative research with a descriptive approach. The informants in this research were 25 class VII students of SMP Negeri 3 Huruna. Data were analyzed using data reduction steps, data presentation, and drawing conclusions. The data collection techniques used were questionnaires, tests and interviews. The results of this research from all student answers show that students made 31.6% reading errors, 32% understanding errors, 25.6% transformation errors, 4.8% processing errors and 6% errors in writing the final answer. So it can be concluded that class VII students at SMP Negeri 3 Huruna experienced errors in understanding based on the visual learning style. Through this research, researchers suggest that teachers create a more enjoyable atmosphere for mathematics learning and provide students with the habit of solving mathematical problems using good and correct solution steps.